Two Nations, Different Regions, Same Challenges: Legal and Political Analysis of Internal Security Threats in Nigeria and Pakistan - Ngboawaji Daniel Nte; Oluka Nduka Lucas; Ridwan Arifin (Jurnal Cita Hukum, 2021)
This study is a modest but objective comparative evaluation of internal security threats facing two sub-regional large countries of Africa and South Asia-Nigeria and Pakistan. Considering the fact that ethnicity, sectarianism and economic instability are fundamental variables of internal security threats in both countries, the study argued that religious extremism has created an unenviable image of both nations in the eyes of the rest of the world, undoubtedly, this has affected both nations adversely. The study also identified inter-regional grievances as potential causes of damages to both federations. Also identified is ethno-sectarian problem as a major security threat to both nations. This in the opinion of the authors will remain a huge impediment to the goals of economic prosperity to both nations. Consequently, the focus of this study is to examine interdependence of these multifaceted challenges and their overall impact on internal security in both countries. To achieve this, the study employed qualitative research method in which analytical approach was used to examine the similarities in the security challenges in Nigeria and Pakistan. Structural questionnaire was used as the instrument for data collection.  The employment of thematic analytic approach was adopted to analyse data collected for the study. The study concludes among others, the need for both countries to individually address these national security threats and find viable solutions to the problems of socio-economic and political reforms and unemployment within a reasonable timeframe to mitigate future threats.Keywords: Internal Security; Ethnicity; Sectarianism; Challenges Dua Bangsa Satu Tantangan: Analisis Politik dan Hukum pada Ancaman Keamanan dalam Negeri (Internal Security) di Nigeria dan PakistanAbstrak Penelitian ini merupakan evaluasi komparatif sederhana namun objektif terhadap ancaman keamanan internal yang dihadapi dua negara besar sub-regional Afrika dan Asia Selatan-Nigeria dan Pakistan. Mempertimbangkan fakta bahwa etnisitas, sektarianisme, dan ketidakstabilan ekonomi adalah variabel fundamental dari ancaman keamanan internal di kedua negara. Penelitian ini berpendapat bahwa ekstremisme agama telah menciptakan citra yang tidak baik dari kedua negara di mata dunia. Tidak diragukan lagi, ini telah mempengaruhi kedua negara secara merugikan. Penelitian ini juga mengidentifikasi kasus-kasus antar-regional sebagai penyebab potensial kerusakan pada kedua federasi. Juga diidentifikasi masalah etno-sektarian sebagai ancaman keamanan utama bagi kedua negara, dimana akan tetap menjadi hambatan besar bagi tujuan kemakmuran ekonomi kedua negara. Fokus penelitian ini adalah untuk menguji saling ketergantungan dari tantangan beragam ini dan dampaknya secara keseluruhan terhadap keamanan internal di kedua negara. Untuk mendapatkan data tersebut, penelitian ini menggunakan metode penelitian kualitatif dimana pendekatan analitik digunakan untuk menguji kesamaan dalam tantangan keamanan di Nigeria dan Pakistan. Kuesioner struktural digunakan sebagai instrumen pengumpulan data. Penggunaan pendekatan analitik tematik diadopsi untuk menganalisis data yang dikumpulkan untuk penelitian ini. Studi ini menyimpulkan antara lain, perlunya kedua negara untuk secara individual mengatasi ancaman keamanan nasional ini dan menemukan solusi yang layak untuk masalah reformasi sosial-ekonomi dan politik dan pengangguran dalam jangka waktu yang wajar untuk mengurangi ancaman di masa depan.Kata Kunci: Keamanan dalam Negeri; Etnisitas; Sektarianisme; Tantangan Две нации, разные регионы, одинаковые вызовы: правовой и политический анализ угроз внутренней безопасности в Нигерии и Пакистане АбстрактныйЭто исследование представляет собой скромную, но объективную сравнительную оценку угроз внутренней безопасности, с которыми сталкиваются две субрегиональные крупные страны Африки и Южной Азии - Нигерия и Пакистан. Учитывая тот факт, что этническая принадлежность, сектантство и экономическая нестабильность являются фундаментальными переменными угроз внутренней безопасности в обеих странах, в исследовании утверждается, что религиозный экстремизм создал незавидный имидж обеих стран в глазах остального мира, несомненно, это повлияло на обе нации неблагоприятно. Исследование также определило межрегиональные жалобы как потенциальные причины ущерба для обеих федераций. Также определена этно-сектантская проблема как серьезная угроза безопасности для обеих стран. Это, по мнению авторов, останется огромным препятствием на пути достижения целей экономического процветания обеих стран. Следовательно, целью данного исследования является изучение взаимозависимости этих многогранных вызовов и их общего воздействия на внутреннюю безопасность в обеих странах. Для достижения этой цели в исследовании использовался качественный метод исследования, в котором использовался аналитический подход для изучения сходства проблем безопасности в Нигерии и Пакистане. Структурная анкета использовалась в качестве инструмента для сбора данных. Для анализа данных, собранных для исследования, был использован тематический аналитический подход. В исследовании, среди прочего, делается вывод о необходимости для обеих стран индивидуально противодействовать этим угрозам национальной безопасности и находить жизнеспособные решения проблем социально-экономических и политических реформ и безработицы в разумные сроки для смягчения будущих угроз.Ключевые слова: внутренняя безопасность; Этническая принадлежность; Сектантство; Вызовы